Eastward radiation of C4 crops from the Hongshan culture core region initiated around 6 ka - Licheng Guo; Qiaowen Zhang; Shiling Yang; Shangfa Xiong; Zihua Tang; Zhe Liu; Jingyi Cui; Linlin Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Cyclic response of severely damaged subway station central columns repaired with ECC jackets under highly variable axial loads - Jia Yang; Peng Deng; Chao Zhang; Renpeng Chen; Shiling Pei (Engineering Structures, 2026)

A low-cost solar disinfection platform: hydrogel-encapsulated benzyl frameworks for continuous in situ H2O2-driven water treatment - Wenjuan Zhang; Lizheng Chen; Xiaojuan Zhao; Shiling Zhang; Chongling Cheng; Juan Du; Kaikai Ba; Bo Wang; Tengfeng Xie; Xuefeng Chu; Gang Liu; Dayang Wang (Water Research, 2026)

Spatiotemporal characteristics of surface longwave radiation over China from the situ measured data - Shiling Zhang; Mengqi Liu; Bo Hu (Atmospheric Research, 2026)

Large-scale vegetation deterioration in response to mid-Holocene cooling across China's Hengduan Mountains - Wenying Jiang; Xiaoxiao Yang; Xiaofang Huang; Lingyu Tang; Enlou Zhang; Shiling Yang (Global and Planetary Change, 2026)

Mechanistic insights into electric-field-induced ice suppression and ion migration in ice-channel-confined NaClO4 electrolyte - Zhenyu Zhang; Dejun Xiong; Zizhen Yan; Yang Guo; Heng Zhang; Shiling Yuan (Chemical Engineering Journal, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Tailoring the structural and textural characteristics of plant-based meat analogues by ice-templating technique - Pan Zhang; Jingwen Sun; Shiling Zhang; Ying Li; Hui Gao; Guowei Shu; Guoliang Li; Xiaolin Yao (Food Research International, 2026)

Enantioselective metabolic mechanism and metabolism pathway of tetraconazole in human liver microsomes: In vitro and in silico study - Shiling Liu; Junqi Zhu; Yu Wang; Wenyu Dai; Ya Zhou; Tengfei Zhang; Xianzhang Yang; Jingjing Wu; Yanmei Liu; Jie Luo; Huihua Tan; Feng Zhao (Environmental Pollution, 2026)

Exploring the Interconnections Between Mitochondrial Dysfunction and Polycystic Ovary Syndrome: A Comprehensive Integrated Analysis - Suqin Zhang; Mingyue Zhu; Shiling Chen (Biochemical Genetics, 2026)

Seismic fragility of segmental tunnels with optimal pairs of intensity measure and engineering demand parameter - Jiaxing Zhou; Zihan Yang; Chao Zhang; Zhixiong Lang; Peng Deng; Ze Chen; Shiling Pei; Renpeng Chen (Soil Dynamics and Earthquake Engineering, 2026)

Vascular normalization by erianin unleashes CAR-T immunotherapy in glioblastoma - Shiling Zhou; Shuyi Qian; Bowen Sun; Peng Shi; Shanni Guo; Changrui Yang; Jiwei Zhang; Yanqing Gong; Fan Yang (Angiogenesis, 2026)

Globally synchronous acceleration of soil formation approximately 12,000 years ago - Licheng Guo; Qiaowen Zhang; Haozhong Xue; Shangfa Xiong; Shiling Yang; Zihua Tang; Linlin Cui; Jingyi Cui; Yongda Wang; Shihao Zhang (Global and Planetary Change, 2026)

Environmental driving forces affect the biogenic amine degradation performance of Lactiplantibacillus plantarum - Shan Qin; Huhu Wang; Xinglian Xu; Zhen Jia; Shiling Lu; Hui Wang; Qiuqin Zhang (Food Bioscience, 2025)

The xylem anatomical structure, physiological characteristics and aromatic components analyses explain the difference of fungal solution induced agarwood formation in Aquilaria sinensis - Shengjiang Pang; Weiwei Zhao; Guihua Huang; Qingbin Jiang; Zaizhi Zhou; Qingqing Zhang; Zuwei Tian; Pei Zhang; Zhongguo Li; Shuokun Deng; Shiling Liu; Baoguo Yang (Trees, 2025)

High-precision U–Pb geochronology of the Guttenberg Carbon Isotope Excursion (GICE) recorded in the Tarim Basin, NW China - Junjie Xu; Jahandar Ramezani; Huaichun Wu; Qiang Fang; Jinghui Guo; Shiling Yang; Shihong Zhang; Tianshui Yang; Zhuyin Chu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Acidic-thermal coupled degradation of tylosin by using magnetic sulfonated resins under microwave irradiation - Caitiao Fang; Wei Zhang; Chunmei Wang; Shiling Li; Xiaomin Dou; Jun Liu (Journal of Environmental Sciences, 2025)

Flow law of particles carried by well-flushing fluid in the annulus and prediction of flushing efficiency based on numerical simulation-interpretable machine learning model - Hanxuan Song; Fuli Li; Binru Li; Jixiang Guo; Jiao Li; Shiling Zhang; Zihan Li (Fuel, 2025)

Research on soil heavy metals pollution in major mineral and grain production composite areas: Status - sources - early warning - Yanyan Li; Zhongyi Tian; Pengyan Zhang; Dongfang Zhang; Shiling Tao; Feng Feng; Mingzhou Qin (Journal of Environmental Chemical Engineering, 2025)

Evolving Therapeutic Landscape of Intracerebral Hemorrhage: Emerging Cutting-Edge Advancements in Surgical Robots, Regenerative Medicine, and Neurorehabilitation Techniques - Danyang Chen; Zhixian Zhao; Shenglun Zhang; Shiling Chen; Xuan Wu; Jian Shi; Na Liu; Chao Pan; Yingxin Tang; Cai Meng; Xingwei Zhao; Bo Tao; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the most serious form of stroke and has limited available therapeutic options. As knowledge on ICH rapidly develops, cutting-edge techniques in the fields of surgical robots, regenerative medicine, and neurorehabilitation may revolutionize ICH treatment. However, these new advances still must be translated into clinical practice. In this review, we examined several emerging therapeutic strategies and their major challenges in managing ICH, with a particular focus on innovative therapies involving robot-assisted minimally invasive surgery, stem cell transplantation, in situ neuronal reprogramming, and brain-computer interfaces. Despite the limited expansion of the drug armamentarium for ICH over the past few decades, the judicious selection of more efficacious therapeutic modalities and the exploration of multimodal combination therapies represent opportunities to improve patient prognoses after ICH.

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Deep learning model based on coupled SWAT and interpretable methods for water quality prediction under the influence of non-point source pollution - Juan Huan; Yixiong Fan; Xiangen Xu; Liwan Zhou; Hao Zhang; Chen Zhang; Qucheng Hu; Wenxin Cai; Haoran Ju; Shiling Gu (Computers and Electronics in Agriculture, 2025)

Basing target enzyme study the enantioselective bioactivity action mechanism of flusulfinam, a novel HPPD inhibitor herbicide - Shiling Liu; Siying Qin; Tengfei Zhang; Heng Zhang; Junqi Zhu; Xiaoli Li; Yuanfu Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2025)

Advancing detection of fungal and mycotoxins contamination in grains and oilseeds: Hyperspectral imaging for enhanced food safety - Zhen Guo; Jing Zhang; Haifang Wang; Shiling Li; Xijun Shao; Lianming Xia; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Recycling of flotation residual carbon from coal gasification fine slag through thermal combustion reaction: Insight into the spatial and temporal multi-scale evolution of typical heavy metals - Yang Guo; Jianjun Wu; Fanhui Guo; Yixin Zhang; Shiling Yuan; Chunan Du; Juan Chen; Meng Lin (Fuel, 2025)

Simultaneous removal of methane and high nitrite from the wastewater by Methylomonas sp. with soluble methane monooxygenase - Yuxuan Sang; Qinqin Hao; Yuechao Zhang; Oumei Wang; Shiling Zheng; Fanghua Liu (Bioresource Technology, 2025)

A new view into the characterization of dissolved organic matter composition in lakes and traceability studies - Juan Huan; Jialong Yuan; Xiangen Xu; Hao Zhang; Xincheng Li; Wenxin Cai; Shiling Gu; Haoran Ju; Liwan Zhou (Science of The Total Environment, 2024)

MicroRNA-451 Regulates Angiogenesis in Intracerebral Hemorrhage by Targeting Macrophage Migration Inhibitory Factor - Shuang Bai; Ge Zhang; Shiling Chen; Xuan Wu; Jiarui Li; Jingxuan Wang; Danyang Chen; Xia Liu; Jiahui Wang; Yuanwei Li; Yingxin Tang; Zhouping Tang (Molecular Neurobiology, 2024)
Intracerebral hemorrhage (ICH) is a subtype of stroke with the highest fatality and disability rate. Up to now, commonly used first-line therapies have limited value in improving prognosis. Angiogenesis is essential to neurological recovery after ICH. Recent studies have shown that microRNA-451(miR-451) plays an important role in angiogenesis by regulating the function of vascular endothelial cells. We found miR-451 was significantly decreased in the peripheral blood of ICH patients in the acute stage. Based on the clinical findings, we conducted this study to investigate the potential regulatory effect of miR-451 on angiogenesis after ICH. The expression of miR-451 in ICH mouse model and in a hemin toxicity model of human brain microvascular endothelial cells (hBMECs) was decreased the same as in ICH patients. MiR-451 negatively regulated the proliferation, migration, and tube formation of hBMECs in vitro . MiR-451 negatively regulated the microvessel density in the perihematoma tissue and affected neural functional recovery of ICH mouse model. Knockdown of miR-451 could recovered tight junction and protect the integrity of blood-brain barrier after ICH. Based on bioinformatic programs, macrophage migration inhibitory factor (MIF) was predicted to be the target gene and identified to be regulated by miR-451 inhibiting the protein translation. And p-AKT and p-ERK were verified to be downstream of MIF in angiogenesis. These results all suggest that miR-451 will be a potential target for regulating angiogenesis in ICH.

Enhanced detection of Aspergillus flavus in peanut kernels using a multi-scale attention transformer (MSAT): Advancements in food safety and contamination analysis - Zhen Guo; Jing Zhang; Haifang Wang; Haowei Dong; Shiling Li; Xijun Shao; Jingcheng Huang; Xiang Yin; Qi Zhang; Yemin Guo; Xia Sun; Ibrahim Darwish (International Journal of Food Microbiology, 2024)

Isolation, purification, characterization, and analysis of the antioxidant activity of antioxidant peptides from walnut milk fermented with Lactobacillus paracasei SMN-LBK - Hui Zhong; Baokun Li; Zhexin Fan; Zhifeng Fang; Yuhui Li; Shiling Lu; Yuechenfei Shen; Wenjing Wang; Ruofan Zhang (Food Bioscience, 2024)

Insights into the silica scaling behaviors in membrane distillation and anti-scaling mechanism of functional polymers - Shideng Yuan; Na Zhang; Shiling Yuan; Zhining Wang (Water Research, 2024)

Comprehensive study of chiral herbicide flusulfinam uptake, translocation, degradation, and subcellular distribution in rice (Oryza sativa L.) - Shiling Liu; Xiaoli Li; Heng Zhang; Siying Qin; Liying Liang; Ying Liao; Junqi Zhu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2024)

Engineering heterogeneous hierarchical hydrogels based on Artemisia sphaerocephala Krasch polysaccharide/whey protein isolate fibrils aqueous two-phase emulsion - Pan Zhang; Qingxia Gou; Shiling Zhang; Xinyue Mei; Xu Zhao; Guoliang Li; Yapeng Fang; Mouming Zhao; Katsuyoshi Nishinari; Xiaolin Yao (Food Hydrocolloids, 2024)

Dual-aspect attention spatial-spectral transformer and hyperspectral imaging: A novel approach to detecting Aspergillus flavus contamination in peanut kernels - Zhen Guo; Jing Zhang; Haifang Wang; Shiling Li; Xijun Shao; Haowei Dong; Jiashuai Sun; Lingjun Geng; Qi Zhang; Yemin Guo; Xia Sun; Lianming Xia; et al. (Postharvest Biology and Technology, 2024)

Pliocene CO2 rise due to sea-level fall as a mechanism for the delayed ice age - Shiling Yang; Yongda Wang; Xiaofang Huang; Minmin Sun; Jingtai Han; Xu Wang; Zuoling Chen; Shihao Zhang; Wenying Jiang; Zihua Tang; Zhaoyan Gu; Shangfa Xiong; et al. (Global and Planetary Change, 2024)

Molecular insights into the adsorption and penetration of oil droplets on hydrophobic membrane in membrane distillation - Shideng Yuan; Xin Yang; Na Zhang; Jiaojiao Zhang; Shiling Yuan; Zhining Wang (Water Research, 2024)

Origin and depositional background of the Holocene black soil in Northeast China: Evidence from grain-size analysis and optically stimulated luminescence dating - Shihao Zhang; Shiling Yang; Shangfa Xiong; Licheng Guo; Yongda Wang; Xiaofang Huang; Minmin Sun; Zhongli Ding (CATENA, 2024)

Microbiome analysis and growth behaviors prediction of potential spoilage bacteria inhabiting harvested edible mushrooms - Fei Xia; Chuchu Zhang; Qiuyue Jiang; Zining Wu; Shiling Cao; Peihong Wu; Yuehua Gao; Xin Cheng (Journal of Plant Diseases and Protection, 2024)

Bacterial community succession and volatile compound changes in Xinjiang smoked horsemeat sausage during fermentation - Honghong Yu; Pingcan Li; Pengcheng Yin; Jixun Cai; Boyu Jin; Haopeng Zhang; Shiling Lu (Food Research International, 2023)

Enhanced east–west climatic contrast in northern China under past global warming: Evidence from paleovegetation records and numerical simulations - Xiaofang Huang; Shiling Yang; Wenying Jiang; Minghu Ding; Yongda Wang; Minmin Sun; Shihao Zhang (Quaternary Science Reviews, 2023)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Spatio-temporal distribution patterns and quantitative detection of aflatoxin B1 and total aflatoxin in peanut kernels explored by short-wave infrared hyperspectral imaging - Zhen Guo; Jing Zhang; Haowei Dong; Jiashuai Sun; Jingcheng Huang; Shiling Li; Chengye Ma; Yemin Guo; Xia Sun (Food Chemistry, 2023)

Response of East Asian summer monsoon to precession change during the mid-Pliocene warm period - Xiaofang Huang; Shiling Yang; Alan Haywood; Julia Tindall; Dabang Jiang; Yongda Wang; Minmin Sun; Shihao Zhang (Quaternary International, 2023)

BrGDGTs-based temperature and hydrological reconstruction from loess-paleosol deposits in the Eastern European Plain since 200 ka - Shihao Zhang; Shiling Yang; Wenying Jiang; Xiaofang Huang; Yongda Wang; Minmin Sun; Licheng Guo; Xiaoxiao Yang; Zhongli Ding (Quaternary Science Reviews, 2023)

Isolation and characterization of an endophytic fungi from Zingiber officinale Rosc. and its activity to promote the growth of tissue culture ginger plantlets in bottles - Shuting Zhang; Yinghong Pei; Jiao Wang; Xiaolong Lin; Zizhong Tang; Lijun Zhou; Tao Chen; Shiling Feng; Chunbang Ding; Yanger Chen; Zhongwei Zhang; Shu Yuan; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Freshwater ecosystem collapse and mass mortalities at the Paleocene-Eocene thermal maximum - Zuoling Chen; Zhongli Ding; Jimin Sun; Shiling Yang; Xijun Ni; Xu Wang; Yongli Wang; Jiangyong Zhang; Wei He (Global and Planetary Change, 2023)

Contribution of air-water interface in removing PFAS from drinking water: Adsorption, stability, interaction and machine learning studies - Shideng Yuan; Xueyu Wang; Zhaoli Jiang; Heng Zhang; Shiling Yuan (Water Research, 2023)

Construction of a dynamic model to predict the growth of Staphylococcus aureus and the formation of enterotoxins during Kazak cheese maturation - Huixue Cai; Sijie Pei; Yan Zhang; Rongrong Liu; Shiling Lu; Baokun Li; Juan Dong; Qingling Wang; Xinrong Zhu; Hua Ji (Food Microbiology, 2023)

Effects of fabrication of conjugates between different polyphenols and bovine bone proteins on their structural and functional properties - Li Pan; Jingya Chen; Huihui Fu; Niannian Wang; Junrong Zhou; Shuyao Zhang; Shiling Lu; Juan Dong; Qingling Wang; Haiyan Yan (Food Bioscience, 2023)

A novel Stauntonia leucantha fruits arabinogalactan: isolation and structural characterization - Hui Li; Tao Gao; Zhonghao Zhang; Jiangping Lei; Junchao Hu; Zizhong Tang; Shiling Feng; Chunbang Ding; Tao Chen; Yanger Chen; Shu Yuan; Ming Yuan (Carbohydrate Polymers, 2023)

A bi-objective optimization for integrated truck operation and storage allocation considering traffic congestion in container terminals - Yi Tao; Shiling Zhang; Changhui Lin; Xiaofan Lai (Ocean & Coastal Management, 2023)

Understanding the transformations of nanoplastic onto phospholipid bilayers: Mechanism, microscopic interaction and cytotoxicity assessment - Shideng Yuan; Heng Zhang; Shiling Yuan (Science of The Total Environment, 2023)

Simulations reveal causes of inter-regional differences in Pliocene climatic periodicity - Xiaofang Huang; Shiling Yang; Alan Haywood; Julia Tindall; Dabang Jiang; Yongda Wang; Minmin Sun; Shihao Zhang; Zhongli Ding (Science Bulletin, 2023)

Respiratory electrogen Geobacter boosts hydrogen production efficiency of fermentative electrotroph Clostridium pasteurianum - Yuechao Zhang; Shiling Zheng; Qinqin Hao; Oumei Wang; Fanghua Liu (Chemical Engineering Journal, 2023)

The differentiation of iron-reducing bacterial community and iron-reduction activity between riverine and marine sediments in the Yellow River estuary - Hongxia Zhang; Fanghua Liu; Shiling Zheng; Lei Chen; Xiaoli Zhang; Jun Gong (Marine Life Science & Technology, 2020)

Pseudomonas aeruginosa phage PaP1 DNA polymerase is an A-family DNA polymerase demonstrating ssDNA and dsDNA 3′–5′ exonuclease activity - Binyan Liu; Shiling Gu; Nengsong Liang; Mei Xiong; Qizhen Xue; Shuguang Lu; Fuquan Hu; Huidong Zhang (Virus Genes, 2016)

Zircon U-Pb dating and geochemical study of the Xianggou granite in the Ma’anqiao gold deposit and its relationship with gold mineralization - LaiMin Zhu; GuoWei Zhang; Ben Lee; Bo Guo; HuJun Gong; Lei Kang; ShiLing Lü (Science China Earth Sciences, 2010)